2022
DOI: 10.1186/s13071-021-05145-y
|View full text |Cite
|
Sign up to set email alerts
|

Local immune response of Canarian Majorera goats infected with Teladorsagia circumcincta

Abstract: Background Due to increased anthelmintic resistance, alternative methods to drugs are necessary to control gastrointestinal nematodes (GINs). Some of the most promising alternatives are based on the immune response of the host, such as the selection of genetically resistant breeds or the use of vaccines against these parasites. Given the limited information available on the immune response against GINs in goats, this study investigated the local immune response of goat kids of an indigenous Can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…(2006) observed a strong negative correlation between female length and the populations of eosinophils, mast cells, and globule leukocytes in the abomasum. Other studies, however, reported that IgA, presumably together with eosinophils, played a role in the control of this infection by influencing parasitological parameters, such as worm length, fecundity, and worm burden ( Hernández et al., 2016 ; Ortega et al., 2022 ; Strain & Stear, 2001 ). The specific or mucosal IgA response was similar in each experimental group towards the end of the experiment, so the difference in worm length could only be associated with the infiltration of immune cells in the abomasal tissue.…”
Section: Discussionmentioning
confidence: 94%
“…(2006) observed a strong negative correlation between female length and the populations of eosinophils, mast cells, and globule leukocytes in the abomasum. Other studies, however, reported that IgA, presumably together with eosinophils, played a role in the control of this infection by influencing parasitological parameters, such as worm length, fecundity, and worm burden ( Hernández et al., 2016 ; Ortega et al., 2022 ; Strain & Stear, 2001 ). The specific or mucosal IgA response was similar in each experimental group towards the end of the experiment, so the difference in worm length could only be associated with the infiltration of immune cells in the abomasal tissue.…”
Section: Discussionmentioning
confidence: 94%
“…These observations have been considered as two mechanisms of natural resistance to infection by these gastric nematodes in small ruminants [25,34] or as immunoprotective mechanisms in vaccination trials using thiol-sepharose chromatography-enriched extracts of H. contortus [35] or O. ostertagi [21,36].…”
Section: Discussionmentioning
confidence: 99%
“…At the end of study, mucus samples were also obtained by superficial scraping of the abomasal mucosa to analyse the local humoral response. The profiles of specific antibodies (IgG and IgA isotypes) against TBSP of adult worms in both types of biological sample (serum or gastric mucus), were performed by two indirect ELISA, as previously described [18,25].…”
Section: Determination Of Systemic and Local Humoral (Igg And Iga Iso...mentioning
confidence: 99%
See 1 more Smart Citation
“…The variation in the prevalence and intensity of infection by these GIPs may be explained by differences in sampling sites and size, years, genetic variations among goat breeds and agro-ecological zone conditions, and variability in management practices, such as feeding, watering, housing, rearing, stocking rate, and health control measures. The presence of subclinical rates of several GIP infections, alone or concurrently, in clinically healthy flocks may be significant for two reasons: First, infected goats can be potential carriers and may influence the extent of disease-precipitating infection in the vulnerable group of kids [ 38 ]. Second, subclinical infection with Eimeria spp.…”
Section: Prevalence Of Gip In Goatsmentioning
confidence: 99%